Illuminate the way : the school leader's guide to addressing and preventing teacher burnout - Mielke, Chase (Arlington, Virginia : ASCD, 2023)
"Chase Mielke provides the best tools and strategies principals and other school leaders need to address teacher burnout and make a real systemic difference"--
Introduction -- Part 1. The Illuminating Leader. Educator well-being 2.0 -- Illuminating mindsets -- Part 2. Distressed to Empowered. Emotional exhaustion 101 -- Reducing workloads -- Autonomy -- Part 3. Disconnected to Engaged. Cynicism 101 -- Relatedness -- Part 4. Defeated to Efficacious. Inefficacy 101 -- Competence -- Conclusion: It starts with one spark.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: School management and organization -- United States -- Psychological aspects; Educational leadership -- United States; Teachers -- Job stress -- United States; Teaching -- Psychological aspects; Burn out (Psychology) -- Prevention; Stress management; Administration scolaire -- États-Unis -- Aspect psychologique; Leadership en éducation -- États-Unis.; Enseignants -- Stress dû au travail -- États-Unis.; Gestion du stress